Reactivity of Myoglobin Reconstituted with Cobalt Corrole toward Hydrogen Peroxide - Koji Oohora (International Journal of Molecular Sciences, 2022)
The protein matrix of natural metalloenzymes regulates the reactivity of metal complexes to establish unique catalysts. We describe the incorporation of a cobalt complex of corrole (CoCor), a trianionic porphyrinoid metal ligand, into an apo-form of myoglobin to provide a reconstituted protein (rMb(CoCor)). This protein was characterized by UV-vis, EPR, and mass spectroscopic measurements. The reaction of rMb(CoCor) with hydrogen peroxide promotes an irreversible oxidation of the CoCor cofactor, whereas the same reaction in the presence of a phenol derivative yields the cation radical form of CoCor. Detailed kinetic investigations indicate the formation of a transient hydroperoxo complex of rMb(CoCor) which promotes the oxidation of the phenol derivatives. This mechanism is significantly different for native heme-dependent peroxidases, which generate a metal-oxo species as an active intermediate in a reaction with hydrogen peroxide. The present findings of unique reactivity will contribute to further design of artificial metalloenzymes.